English: English - Irma Damajanti; Ardhana Riswarie; Lulu Lusianti Fitri; RR Sri Wachyuni; Miryam Wedyaswari (ITB Journal Publisher, LPPM ITB, 2021)
Therapeutic uses of art have been acknowledged since even before the emergence of art therapy as a discipline and profession. Over the last couple of years, the Psychology of Art course managed under the Visual Art Study Program ITB has included discussion and therapeutic artmaking practice for students from all over the university. During the beginning of the Covid-19 pandemic, the delivery of therapeutic artmaking practice in the classroom had to be adjusted. Therefore, a video guide was created to help the students to follow the course activities. This paper describes the process and the theoretical background of making the video guide as well as discussing some of the students’ reports using the self-concept framework and the effectiveness of distance therapeutic artmaking activities. The preliminary study used a quasi-experimental approach, specifically a pre-experimental design, towards Psychology of Art students in 2020. The data used included verbal reports and images, which were analyzed qualitatively using codification and content analysis with two raters to discuss the findings. The results showed that the activity was impactful towards students’ self-concept. In some findings, the participants elaborated how the activity had impacted them positively. In the future, this model of distant therapeutic artmaking can be further developed and distributed to give benefits to a larger audience.